S2k guidelines for the diagnosis and treatment of type B aortic dissection - Torsello, G.; Czerny, M.; Grundmann, R. T.; Krankenberg, H.; Nikol, S.; Puls, R.; Raddatz, A.; Schelzig, H.; Schmieder, Roland; Zahn, R. (Gefässchirurgie, 2019)
Type B aortic dissection is a relatively rare clinical picture that involves many fields of medicine and requires a multidisciplinary approach. In this report, the disciplines involved constitute the most important aspects of the new S2k guidelines for the diagnosis and treatment of type B aortic dissection. More specifically, the definition and epidemiology, the clinical and technical diagnostic methods, in addition to the imaging methods, are presented, and recommendations for the individual topics based on scientific studies and expert opinion are given. In the guidelines, the various procedures related to the main conservative and surgical treatment regimes in the acute, subacute, and chronic phases of the condition are dealt with.
CRIS-Team WoS Importer:2019-02-27